MANAJEMEN PENDIDIKAN ISLAM DI MTs PUTERI SUNNIYYAH SELO: STUDI KUALITATIF - Rahayu, Sucik (Jurnal Ilmiah Pendidikan dan Keislaman, 2025)
This study aims to examine the management of Islamic education at MTs Puteri Sunniyyah Selo. The approach used is qualitative with in-depth interview, observation, and documentation techniques. The results of the study show that the management of Islamic education in this madrasah is based on the principle of integration between Islamic values and modern academic development. The three main components, namely curriculum management, student management, and human resources, show good synergy, despite facing limited facilities and infrastructure. Collaborative strategies, transformational leadership, and foundation support are the main strengths in carrying out managerial functions. Key recommendations include strengthening management digitalization, continuous training for educators, developing technology-based evaluation systems, and increasing external cooperation for sustainability and improving the quality of education. This study contributes both from theoretical and practical aspects in the development of Islamic-based education management in the madrasah environment.